Development Strategy Of Tourism Objects In Thousand Islands Of Jakarta Special Region Province - Srining Ayu; Yudi Rusfiana; Andi Masrich (Sean Institute, 2025)
This research is motivated by the lack of development of tourist attractions on the island of profit Java in the Thousand Islands Administrative Regency. The purpose of the study was to analyze and find out the strategy of the Thousand Islands Administrative Regency Tourism and Creative Economy Service Tribe in Developing Java Island Tourism Objects. Then using descriptive qualitative methods. The data sources used are primary data and secondary data. Data collection techniques through observation, interviews and documentation. The results of this study indicate that the development of tourist attractions by the Tourism and Creative Economy Office Tribe in the Thousand Islands Administrative Regency when viewed from the theory used, namely the theory of tourism development from Ketut Suwena & Gusti, on indicators Attractions have not gone well, facilities and accessibility are quite adequate, then also in developing services and additions are not maximally carried out by the Thousand Islands Administrative Regency Tourism and Creative Economy Office Tribe. The influencing factors consist of internal factors and external factors which are then continued by determining the strategies that should be carried out for success based on SWOT analysis obtained strategic issues, among others: Optimizing cooperation with third parties in the development of tourist attractions of Untung Java, optimizing the functions and programs of the Tourism and Creative Economy Service Unit in the development of tourist attractions on the island of Untung Java, increasing the use of technology in promoting and providing tourism information. And improve supporting infrastructure on the tourist attraction of the island of Untung Jawa which is managed by the government.